Beyond the gender binary: a survey of gender marginalization and social boundaries in Australian jazz and improvisation - Goh, Talisha; Hope, Cat; Devenish, Louise; Barrett, Margaret S.; Canham, Nicole; Burke, Robert L.; Hall, Clare (Frontiers in Psychology, 2024)
Jazz and improvisation have typically been associated with ideals of freedom and liberty; however, in practice these genres are known to be constrained by entrenched patterns of male domination and gender discrimination. Despite a large number of qualitative accounts evidencing persistent sexism and gender exclusion in the field, there exists a lack of empirical data to assess the scale of this phenomenon and substantiate smaller-scale research on gender inequality. In this paper, we employ boundary theory to report on a quantitative investigation of gender marginalization in jazz and improvisation in the Australian context, positioning gender as a symbolic boundary resulting in the social exclusion and marginalization of gender diverse individuals and women. An anonymous survey (n=124) was run over a period of five months, to explore the beliefs, attitudes, and experiences concerning gender, of people participating in Australian jazz and improvisation. A means comparison found that gender was a statistically significant indicator (p ≤0.05) on almost all measures, with gender diverse respondents significantly more likely to report the effects of marginalization than their (cisgender) counterparts. Additionally, the results indicated contrasting forms of musical engagement and marginalization across gender groups, with women perceiving exclusion to a lesser extent than gender diverse practitioners, and differing in their opinions regarding work opportunities. Lastly, a widespread but historically unspoken awareness of sexual harassment in the Australian jazz and improvisation industry was reported by all genders. This paper concludes with three recommendations for future research, policy and practice: 1. Specific targeted strategies are needed to address the manifold and complex forms of marginalization experienced by gender diverse people; 2. Heightened institutional visibility for marginalized groups is needed to change gendered narratives and highlight awareness of inequities; and 3. Enhanced safety measures are critically needed to address sexual harassment throughout the industry.